2020
DOI: 10.2196/17142
|View full text |Cite
|
Sign up to set email alerts
|

A Smartphone App for Self-Management of Heart Failure in Older African Americans: Feasibility and Usability Study

Abstract: Background Mobile health (mHealth) apps are dramatically changing how patients and providers manage and monitor chronic health conditions, especially in the area of self-monitoring. African Americans have higher mortality rates from heart failure than other racial groups in the United States. Therefore, self-management of heart failure may improve health outcomes for African American patients. Objective The aim of the present study was to determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
78
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(84 citation statements)
references
References 30 publications
0
78
0
6
Order By: Relevance
“…On the basis of our analysis, Black patients used the technology 21 fewer times on average during the study period compared with non-Black patients with otherwise similar characteristics. As in our data set, Black race is not highly correlated with other features, this study adds to the evidence that technology design may need to be better tailored for this population [ 14 ]. Although our findings contribute to the emergent and growing literature on racial disparities in technology use, this area is still understudied.…”
Section: Discussionmentioning
confidence: 61%
“…On the basis of our analysis, Black patients used the technology 21 fewer times on average during the study period compared with non-Black patients with otherwise similar characteristics. As in our data set, Black race is not highly correlated with other features, this study adds to the evidence that technology design may need to be better tailored for this population [ 14 ]. Although our findings contribute to the emergent and growing literature on racial disparities in technology use, this area is still understudied.…”
Section: Discussionmentioning
confidence: 61%
“…While there are several patient-centered heart failure apps available, few have been designed by clinicians who care for patients with heart failure or have been evaluated with a scientific assessment or publication in a medical journal to date [8,9,[15][16][17]. Several well-designed, previously published feasibility studies utilized a more resource-intensive telemonitoring approach (such as a chest strap that monitors physiological data and accelerometer or blood pressure monitoring) in combination with a smartphone app [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review identified few high-quality commercially available mHealth apps for managing heart failure and a paucity of peer-reviewed literature assessing the experiences, functionality, and efficacy of apps [ 12 ]. However, with more interventions using mHealth as a medium for intervention delivery, its acceptability and usability have been reported [ 16 , 24 , 25 ]. Although many heart failure apps are currently available, a systematic search [ 26 ] found that several apps need further redesign or development to engage users in self-management behaviors.…”
Section: Introductionmentioning
confidence: 99%